О выражении страха лексемами с корнем страх / страш-(на материале русских литературных текстов и их перевода на польский язык) - Kiper, Milena (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The article presents linguistic ways of expressing fear in Russian literature. We discuss Russian sentences containing lexemes страх, страшный, страшно. We compare Polish equivalents to the original sentences.
Keywords: страх; выражение эмоций; русский и польский языки; fear; expressing emotions; Russian; Polish